Modeling of Self-Organizing Systems: An Overview - Holzer, Richard; Wüchner, Patrick; de Meer, Hermann (Electronic Communications of the EASST, 2010)
This paper gives a systematic overview on modeling formalisms suitable for modeling self-organizing systems. We distinguish between micro-level modeling and macro-level modeling. On the micro level, the behavior of each entity and the interaction between different object must be described by the model. Macrolevel modeling abstracts from the individual entities and only looks at the behavior of the system variables of interest. The differentiations between discrete and continuous time and between discrete and continuous state space lead to different descriptions of the model.